Medical student education simulation competitions. (23rd October 2022) - Pajor, Michael; Xie, Nicholas; Podolej, Gregory
Abstract: Background: Sim Wars is a simulation‐based competition wherein teams of medical trainees are presented a clinical scenario and provide patient care in front of a live audience. This non‐traditional educational offering is a form of serious games in medical education and allows for experiential learning via direct observation. Although a well‐described educational modality within graduate medical education, there is a dearth of literature regarding Sim Wars as an educational tool within undergraduate medical education. In this paper, we aim to share student perspectives after participating in Sim Wars. Approach: The Sim Wars competition was designed as a double‐elimination bracket tournament with arena‐style direct observation to maximise student engagement. Teams were provided formative feedback in areas of medical knowledge, clinical management and communication skills. A total of 64 students participated in a regional Sim Wars tournament over the course of 2 years. Evaluation: A total of 36 students completed Likert‐based surveys immediately after the Sim Wars competition. Quantitative data and open‐ended responses were analysed. Fourteen students participated in focus groups held a few months after Sim Wars regarding their experiences during the competition. Thematic analysis was systematically performed on the qualitative data. Implication: Participation in Sim Wars was viewed by students as a high‐yield learning experience that increased competence on subsequent clinical rotations. We conclude that this form of serious game can be a highly beneficial educational format for medical students especially if they spend time preparing for the competition and receive structured feedback on their performance.